PEMBENTUKAN KARAKTER DISIPLIN SISWA MELALUI PENERAPAN TATA TERTIB SEKOLAH DI SEKOLAH MENENGAH PERTAMA ISLAM DARUSSA’ADAH PONCOKUSUMO MALANG - Ilham Ali Yafie; Chalimatus Sa’dijah; Mohammad Murtadho (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
The character of discipline is something everyone needs to have. Because with a character discipline can make a person's life become more organized and orderly in all aspects. The goal in shaping the character of discipline is to develop a person's basic potential to behave orderly and orderly in everyday life. Research titled